(untitled) (JÓVENES EN LA CIENCIA, 2025)
Conducting testing on websites in working conditions allows identifying missed errors, mitigates the risk of their recurrence, and minimizes the impact of such errors on users’ experience. The article discusses an approach to testing key functions of educational and e-commerce websites using a combination of usability and functional testing methods. This approach enables finding errors in key websites’ functions, reducing the risk of missing errors on educational and e-commerce websites and increasing users’ confidence. The study includes some experimental data for risk score evaluation for missed errors on educational and e-commerce websites and recommended risk mitigation measures.